Cryptotanshinone Inhibits the Growth of HCT116 Colorectal Cancer Cells Through Endoplasmic Reticulum Stress-Mediated Autophagy - Xiaojing Fu; Wenwen Zhao; Wenwen Zhao; Kangkang Li; Jingyi Zhou; Xuehong Chen (Frontiers Media S.A., 2021)
Among cancers, colorectal cancer (CRC) has one of the highest annual incidence and death rates. Considering severe adverse reactions associated with classical chemotherapy medications, traditional Chinese medicines have become potential drug candidates. In the current study, the effects of cryptotanshinone (CPT), a major component of Salvia miltiorrhiza Bunge (Danshen) on CRC and underlying mechanism were explored. First of all, data from in vitro experiments and in vivo zebrafish models indicated that CPT selectively inhibited the growth and proliferation of HCT116 and SW620 cells while had little effect on SW480 cells. Secondly, both ER stress and autophagy were associated with CRC viability regulation. Interestingly, ER stress inhibitor and autophagy inhibitor merely alleviated cytotoxic effects on HCT116 cells in response to CPT stimulation, while have little effect on SW620 cells. The significance of apoptosis, autophagy and ER stress were verified by clinical data from CRC patients. In summary, the current study has revealed the anti-cancer effects of CPT in CRC by activating autophagy signaling mediated by ER stress. CPT is a promising drug candidate for CRC treatment.